(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
This article aims at the descriptive historical study of grammar school textbooks used in the early stages of primary education in Venezuela during the period 1820-1930, as well as also the pedagogical trends that are embedded, authors and the legal framework that holds them. Documentary sources are represented by four textbooks particular of that historical period, contextualized in the laws, decrees and resolutions issued during that period which shows the subjective influence of trends and acting pedagogical ideas in the Venezuelan educational circumstances. For the design of this study tackled the documentary method under the focus of social history. The product of this inquiry consists of the study of educational and discursive orientations of textbooks of grammar in the period pointed out, supported by the political, ideological, economic, social and cultural contextual aspects that explain his appearance.